Enhancing Critical Thinking through Ethnoscience-Integrated Problem-Based Learning: A Comparative Study in Secondary Education - Yusuf Sarkingobir; Abdulaziz Bello (International Journal of Ethnoscience and Technology in Education, 2024)
This study investigates the impact of integrating ethnoscience with problem-based learning (PBL) on the enhancement of critical thinking skills among secondary school students. Employing a nonequivalent control group design with purposive sampling, the research involved 66 students from a Nigerian secondary school, divided into experimental (n=31) and control (n=35) groups. The experimental group engaged in a PBL curriculum enriched with ethnoscience, while the control group received traditional expository teaching. The study aimed to bridge the gap in current educational practices by incorporating cultural relevance into science education, thus making learning more meaningful and directly applicable to students' lives. Results indicated a significant improvement in the critical thinking abilities of the experimental group, as evidenced by their pretest and posttest scores, compared to the control group. The findings underscore the effectiveness of the ethnoscience-integrated PBL approach in fostering higher-order thinking skills, suggesting a notable advancement over conventional teaching methods. This research contributes to the educational literature by demonstrating the benefits of combining ethnoscience and PBL, advocating for a shift towards more dynamic, student-centered, and culturally relevant teaching strategies. The study highlights the importance of contextual learning experiences and suggests further exploration across various disciplines and educational levels to validate the approach's effectiveness and applicability.